Convolution Properties for Some Subclasses of Meromorphic Functions of Complex Order - M. K. Aouf; A. O. Mostafa; H. M. Zayed (Abstract and Applied Analysis)
Making use of the operator Lυ for functions of the form fz=1/z+∑k=1∞akzk-1, which are analytic in the punctured unit disc U∗={z:z∈C and 0<|z|<1}=U∖{0}, we introduce two subclasses of meromorphic functions and investigate convolution properties, coefficient estimates, and containment properties for these subclasses.